KONTRIBUSI KEKUATAN GENGGAMAN DAN KELENTURAN PINGGANG DENGAN KEMAMPUAN SERVIS ATLET TENIS - Lolia Manurizal (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this research is to know how big contribution of grip strength and flexibility of waist to service ability atlet tennis PTL UNP.To obtain research data used handgrip dynamometer, flexometer test andservice capability. The data obtained were analyzed by simple and multipleproduct moment, to determine the contribution of the use of determinant frequency The result of this research is grip strength have significantrelation with service capability, marked with result obtained, that rt> rtabel has contribution equal to 51%. The flexibility of the waist has a significant relationship with serviceability, characterized by the results obtained, ie rhitung> rtabel, has a contribution of 31%. While the strength of grip and flexibility of waist to service ability at tennis athlete PTL UNP, marked with result obtained rhitung> rtabel, meaning Ho rejected and Ha accepted and have contribution 37%.